Novel anesthetic technique for combined intracavitary and interstitial brachytherapy for cervix cancer in an outpatient setting - Leong, Yiat Horng; Tan, Kenneth Hock Soon; Ai Choo, Bok; Koh, Vicky Yaling; Tang, Johann I-Hsiung (Journal of Contemporary Brachytherapy, 2017)
Purpose : To determine the feasibility and safety of outpatient combined intracavitary and interstitial brachytherapy for cervix cancer with sedation and local anesthesia. Material and methods : We included patients diagnosed with non-metastatic cervix cancer and have completed brachytherapy between December 2015 and December 2016. Moderate to deep sedation was achieved using intravenous midazolam, propofol, fentanyl, and oxycodone. Local anesthesia was achieved with 2% lignocaine gel and a paracervical block containing a mixture of 1% ropivacaine, 2% lignocaine, and 1 : 1,000 adrenaline. Ceftriaxone and ondansetron were given prophylactically. Physiologic monitoring was performed throughout and pain scores were recorded using the Numeric Rating Scale. Follow-up was conducted at 8 weeks from the last fraction of brachytherapy. The feasibility and safety endpoints were a post-anesthesia discharge score (PADS) of 9 or above, and no grade 3 or above adverse events, respectively. Results : A total of thirty-five brachytherapy insertions were carried out on nine patients. The median age of the patients was 56 years (range, 40-65). Eight patients had American Society of Anesthesiologists’ physical status of I or II, and one had a status of III. The mean duration of the insertion was 39 minutes (standard deviation [SD] = 14), during which no adverse events occurred. There was no significant nausea or vomiting post-sedation. The median pain scores post-insertion and during recovery were 0 (range, 0-6) and 0 (range, 0-7), respectively. At discharge, all patients had pain scores of 0 and maximum PADS of 10. The mean time to discharge was 4.1 hours (SD = 0.95). There were no brachytherapy-related admissions or complications. Conclusions : Outpatient combined intracavitary and interstitial brachytherapy for cervix cancer with sedation and local anesthesia is feasible and safe. This could potentially lead to significant cost savings.